From the seismic cycle to long‐term deformation: linking seismic coupling and Quaternary coastal geomorphology along the Andean megathrust. Issue 2 (9th February 2017) - Saillard, M.; Audin, L.; Rousset, B.; Avouac, J.‐P.; Chlieh, M.; Hall, S. R.; Husson, L.; Farber, D. L.
Abstract: Measurement of interseismic strain along subduction zones reveals the location of both locked asperities, which might rupture during megathrust earthquakes, and creeping zones, which tend to arrest such seismic ruptures. The heterogeneous pattern of interseismic coupling presumably relates to spatial variations of frictional properties along the subduction interface and may also show up in the fore‐arc morphology. To investigate this hypothesis, we compiled information on the extent of earthquake ruptures for the last 500 years and uplift rates derived from dated marine terraces along the South American coastline from central Peru to southern Chile. We additionally calculated a new interseismic coupling model for that same area based on a compilation of GPS data. We show that the coastline geometry, characterized by the distance between the coast and the trench; the latitudinal variations of long‐term uplift rates; and the spatial pattern of interseismic coupling are correlated. Zones of faster and long‐term permanent coastal uplift, evidenced by uplifted marine terraces, coincide with peninsulas and also with areas of creep on the megathrust where slip is mostly aseismic and tend to arrest seismic ruptures. We conclude that spatial variations of frictional properties along the megathrust dictate the tectono‐geomorphological evolution of the coastal zone and the extent of seismic ruptures along strike. Key Points: Peninsulas are seismic barriers and show locally high Quaternary uplift rates (>0.4 m/ka) They tend to form above aseismically sliding areas and are permanent over multiple seismic cycles These dynamic features reflect anelastic deformation of the fore arc in response to the subduction seismic cycle